Stafne Bone Defect Involving the Ascending Ramus. Issue 4 (June 2019) - Lee, Kevin C.; Yoon, Angela J.; Philipone, Elizabeth M.; Peters, Scott M.
Abstract : Abstract: The Stafne bone defect (SBD) classically presents as a well-defined, radiolucent lesion in the molar-mandibular angle region beneath the level of the mandibular canal. Due in large part to this prototypical appearance, most cases of SBDs are radiographically diagnostic without the need for tissue biopsy. A diagnostic challenge may arise, however, when the SBD occurs in other locations in the mandible. The authors report a case of a 57-year-old male who presented with a SBD of the left ascending ramus. The lesion was found incidentally on a panoramic radiograph. Additional imaging studies confirmed a lingual concavity of the mandibular bone consistent with a SBD, and a retrospective study of the patient's records revealed the presence of the lesion 5 years prior without any radiographic alterations. To date, only 10 documented cases of an SBD involving the ascending ramus have been reported. The rarity of such a presentation may obscure the diagnosis and lead to unwarranted surgical procedures. It is important to recognize atypically located SBDs, because unlike other radiolucent lesions, imaging studies are diagnostic. With proper diagnosis, additional surgical procedures and any associated morbidities can be avoided. Abstract : Supplemental Digital Content is available in the text